(untitled) (PERcursos Linguísticos, 2022)
Based on the enunciative-discursive approach (Bakhtin and the Circle) this article was based on the reflection about the didactic proposal for the development of understanding about the different approaches of Translation Studies, through the use of specific term-signs in Libras to refer to the languages involved in translation, as: source text and target text, base text and meta text, departure text and arrival text, translation text and translated text. The purpose was to analyze the collective creations in the process of conceptual elaboration about the languages involved in translation in teaching situations and retrospective reports produced by teacher-trainers of translators. The results show that there are positive effects of knowledge development on the currents of Translation Studies and meta-reflection of translators in formation, because the convention of a sign-term in sign language makes it imaginatively possible to associate the concept of the term with its epistemological fundament.